2011
DOI: 10.1590/s0102-311x2011000700014
|View full text |Cite
|
Sign up to set email alerts
|

Social epidemiology of a large outbreak of chickenpox in the Colombian sugar cane producer region: a set theory-based analysis

Abstract: There are few social epidemiologic studies on chickenpox outbreaks, although previous findings suggested the important role of social determinants. This study describes the context of a large outbreak of chickenpox in the Cauca Valley region, Colombia (2003 to 2007), with an emphasis on macro-determinants. We explored the temporal trends in chickenpox incidence in 42 municipalities to identify the places with higher occurrences. We analyzed municipal characteristics (education quality, vaccination coverage, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
4
0
4
Order By: Relevance
“…Between 2003 and 2007 a large outbreak was reported from Colombia where both adults and children were affected. 8 In the month of December 2007 an outbreak reported from India (Ambala). From the studies it was observed that out of one lakh VZV patient's 4-9 numbers of patients dies and out of this 4-9 numbers 81-85% adults.…”
mentioning
confidence: 99%
“…Between 2003 and 2007 a large outbreak was reported from Colombia where both adults and children were affected. 8 In the month of December 2007 an outbreak reported from India (Ambala). From the studies it was observed that out of one lakh VZV patient's 4-9 numbers of patients dies and out of this 4-9 numbers 81-85% adults.…”
mentioning
confidence: 99%
“…Esto podría estar asociado también con un menor nivel de educación de los padres. Al respecto, un estudio en población colombiana encontró relación entre menor calidad de educación y mayor incidencia de casos de varicela (15) . Esto podría explicar el incremento de casos de varicela complicada en los últimos años y el porqué del incremento de los casos de infección secundaria de piel y partes blandas (Figura 3); y nos orientan a plantear que las estrategias de promoción de la salud no son del todo efectivas dado que el cuidado en casa de los niños con varicela no son los más adecuados, lo que predispone a que se compliquen.…”
Section: Discussionunclassified
“…Sin embargo, los casos de varicela con inmunosupresión o comorbilidades (casos incluidos como varicela severa), representan una proporción muy baja en comparación a lo descrito en países desarrollados (9,12) . El tipo de complicación por varicela más frecuente corresponde a las infecciones secundarias de piel y partes blandas, al igual que en otros estudios con poblaciones parecidas al nuestro (3,15,17) , siendo los diagnósticos de celulitis e impétigo más frecuentes, que representan el 63% de todos los casos de varicela complicada y el 89% de todos los casos de infección secundaria de piel o partes blandas, por lo que deberíamos estar alerta en los casos con fiebre, hipotensión e insuficiencia renal, que constituyen el cuadro de shock por toxinas del Staphilococcus aureus o del Streptococcus piógenos que están asociadas con mayor mortalidad, por lo que sugerimos evaluaciones clínicas permanentes apoyados con exámenes de laboratorio (18,19) . El estudio tiene limitaciones.…”
Section: Discussionunclassified
“…Permite explorar varias posibles rutas causales, incluyendo valores extremos, a diferencia de los métodos estadísticos convencionales (18). La lógica causal del Qca es similar a los conceptos de causa suficiente y causa necesaria (21,22).…”
Section: Análisis Comparativo Cuantitativo (Qca)unclassified